Exploring modulations in T-cell receptor-mediated T-cell signaling events in systemic circulation and at local disease site of patients with tubercular pleural effusion: An attempt to understand tuberculosis pathogenesis at the local disease site - Sharma, Bhawna; Rathour, Diwakar; Uddin, Sumbul; Joshi, Beenu; Chauhan, Devendra Singh; Kumar, Santosh (Frontiers in Medicine, 2022)
T cells are crucial for pathogenesis as well as control for tuberculosis (TB). Although much is known about the signalling pathways which are required for the activation of T cells during acute infection but the way these cells respond during persistent of infection still remained elusive. Therefore, it is rationale to understand T cell activation during tuberculous pleural effusion (TPE), which is similar to bacterial persistency system. Herein, we will employ T cell receptor (TCR) based approaches for studying events of T cell activation pathways in cells of blood and pleural fluid among patients with TPE. We performed spectrofluorimetric analysis to study effect of M. tuberculosis antigens, ESAT-6 and Ag85A stimulation on intracellular calcium levels, Phosphorylation levels of ZAP-70 (Zeta-chain-associated protein kinase 70), PKC- θ (Protein kinase C theta), Erk1/2 (Extracellular signal-regulated kinase 1 and 2) and p-38 two important members of MAPKs (Mitogen activated Protein kinases) in CD3 and CD28 induced cells of blood and pleural fluid of same patients with TPE by western blotting. Patients with non-TPE were also included as matching disease controls in this study. We observed significantly higher intracellular calcium levels, Phosphorylation levels of ZAP-70, Erk1/2 and p-38 in CD3 and CD28 induced cells of pleural fluid as compared to the blood cells of same patients with TPE. Alteration in the activation of these events has also been noted after stimulation of ESAT-6 and Ag85A. Present study demonstrated up-regulated activation of TCR mediated T cell signalling events at local disease site (Pleural fluid) as compared to the blood sample of TB pleurisy patients which could be involved in T-cell dysfunctioning during the progression of the disease and also could be responsible for Th 1 dominance at local disease site in patients with TPE.